PENGARUH METODE PEMBELAJARAN DAN JENIS KELAMIN TERHADAP HASIL BELAJAR ANAK DI TK ABA KOTA SEMARANG - Mufnaety S.Ch (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2011)
The study aims to determine the effect of teaching methods and learning outcomes of sex to kindergartners. Specifically the study aims to describe the methods of learning, gender, and learning outcomes and teaching methods and analyze the influence of gender on learning outcomes of children in kindergarten. The method of learning is the way in which teachers in the learning process to achieve the objectives of activities. Learning methods referred to in this study is the method of play and storytelling. Gender is defined as the biological and anatomical differences in body chemical composition between men and women who are considered influential in the development and intellectual capacity emotional respectively. The results of learning are obtained through assessment tests, which are grouped into three domains, namely kognitive, affective and psychomotor. Theoritically, the interaction of children with the learning methods of play the role remind one another duties as agreed in the game. This condition is easier for the child in games or understand the procedure and given the role and functions of each. But not all children feel and get the same role in a game so the experience they have got is different. Thus play role method can affect learning outcomes. Based on research results showed that this method of learning and gender had no interactive effects on learning outcomes.